The transformation of sum of sine functions into product form can be derived in trigonometry by the trigonometric identities. $x$ and $y$ are two angles of two right triangles, then the sine functions with the both angles are written as $\sin{x}$ and $\sin{y}$ respectively.

Now, add the sin functions $\sin{x}$ and $\sin{y}$ for expressing them in summation form.

$\implies$ $\sin{x}+\sin{y}$

Actually, it is not possible to simplify the trigonometric expression $\sin{x}+\sin{y}$ directly but it is not impossible. If we make each term expandable, then it is possible to convert them into product form.

Take, $x = a+b$ and $y = a-b$. Now, substitute the equivalent values in the trigonometric expression.

$\sin{x}+\sin{y}$ $\,=\,$ $\sin{(a+b)}$ $+$ $\sin{(a-b)}$

According to the angle sum and angle difference of sin functions, the functions $\sin{(a+b)}$ and $\sin{(a-b)}$ can be expanded.

$=\,\,\,$ $\Big(\sin{a}\cos{b}$ $+$ $\cos{a}\sin{b}\Big)$ $+$ $\Big(\sin{a}\cos{b}$ $-$ $\cos{a}\sin{b}\Big)$

Now, simplify the trigonometric expression by the fundamental mathematical operations.

$=\,\,\,$ $\sin{a}\cos{b}$ $+$ $\cos{a}\sin{b}$ $+$ $\sin{a}\cos{b}$ $-$ $\cos{a}\sin{b}$

$=\,\,\,$ $\sin{a}\cos{b}$ $+$ $\sin{a}\cos{b}$ $+$ $\cos{a}\sin{b}$ $-$ $\cos{a}\sin{b}$

$=\,\,\,$ $2\sin{a}\cos{b}$ $+$ $\require{cancel} \cancel{\cos{a}\sin{b}}$ $-$ $\require{cancel} \cancel{\cos{a}\sin{b}}$

$\,\,\, \therefore \,\,\,\,\,\,$ $\sin{x}+\sin{y}$ $\,=\,$ $2\sin{a}\cos{b}$

Therefore, it is successfully transformed the sum of the sin functions into product form but the product form is in terms of $a$ and $b$. So, they should be expressed in terms of $x$ and $y$.

We have taken that $x = a+b$ and $y = a-b$ in the second step of the derivation.

Now, add both equations to find the value of $a$.

$\implies$ $x+y$ $\,=\,$ $(a+b)+(a-b)$

$\implies$ $x+y$ $\,=\,$ $a+b+a-b$

$\implies$ $x+y$ $\,=\,$ $a+a+b-b$

$\implies$ $x+y$ $\,=\,$ $\require{cancel} 2a+\cancel{b}-\cancel{b}$

$\implies$ $x+y \,=\, 2a$

$\implies$ $2a \,=\, x+y$

$\,\,\, \therefore \,\,\,\,\,\,$ $a \,=\, \dfrac{x+y}{2}$

Now, subtract the equation $y = a-b$ from the equation $x = a+b$ for getting the value of $b$ in terms of $x$ and $y$.

$\implies$ $x-y$ $\,=\,$ $(a+b)-(a-b)$

$\implies$ $x-y$ $\,=\,$ $a+b-a+b$

$\implies$ $x-y$ $\,=\,$ $a-a+b+b$

$\implies$ $x-y$ $\,=\,$ $\require{cancel} \cancel{a}-\cancel{a}+2b$

$\implies$ $x-y \,=\, 2b$

$\implies$ $2b \,=\, x-y$

$\,\,\, \therefore \,\,\,\,\,\,$ $b \,=\, \dfrac{x-y}{2}$

In the previous step, we have derived that $\sin{x}+\sin{y}$ $\,=\,$ $2\sin{a}\cos{b}$. Now, replace the values of $a$ and $b$ in the equation.

$\,\,\, \therefore \,\,\,\,\,\,$ $\sin{x}+\sin{y}$ $\,=\,$ $2\sin{\Big(\dfrac{x+y}{2}\Big)}\cos{\Big(\dfrac{x-y}{2}\Big)}$

Therefore, the sum of the sin functions is successfully transformed into product form of the trigonometric functions and it is called as the sum to product identity of the sine functions.

The sum to product formula of sin functions can also be derived in terms of $C$ and $D$ by taking $C$ instead of $x$ and $D$ instead of $y$.

$\,\,\, \therefore \,\,\,\,\,\,$ $\sin{C}+\sin{D}$ $\,=\,$ $2\sin{\Big(\dfrac{C+D}{2}\Big)}\cos{\Big(\dfrac{C-D}{2}\Big)}$

Similarly, you can also derive the transformation of sum into product identity of sin functions in terms of any angles.

Latest Math Topics

Latest Math Problems

Email subscription

Math Doubts is a best place to learn mathematics and from basics to advanced scientific level for students, teachers and researchers.
Know more

Learn how to solve easy to difficult mathematics problems of all topics in various methods with step by step process and also maths questions for practising.